Development of E-Module Assisted by Book Creator in Javanese Language Learning Materials of Uploading Language in Grade II of Elementary School II Ariyojeding - Yaniar , Velien Zenita; Jadmiko , Rahmad Setyo (Universitas Nusantara PGRI Kediri, 2025)
The research is motivated by initial findings during observation, although e-modules have been implemented, there is still a need for further development by utilizing Book creator technology. The media that is often used in SD Negeri II Ariyojjeding, especially in class II, is the LKS book. This study aims to improve the quality of learning by introducing new innovations in the form of e-modules assisted by Book creators. This study uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Validity is determined by media expert validation, material expert validation, and language expert validation. The assessment from the media expert scored 90% in the